(3ESJQGJjLjI GdehGQO GdHTQjI (B/s - (3JTGfOG, CThcs; (3GdNRGei, YHO GdMce GMeO s; (3cGHQG, TdHG s ((3GdbGgQI(B: s (3OGQ GdaLQ ddfTQ h GdJhRjY(B, s, 2002)
(3fThA SjfGQjh GdehGQO GdHTQjI h JWhQ GSJQGJjLjJgG eY GdJWQb Gdi NWhGJ Gdgjcd GdeYeGQj HJfGhd HfGA QDjI GdehGQO GdHTQjI h GdeSM GdeJaMU ddHjFI h eQGLYI GdcaGAGJ h GdehGQO h QDjI NWW GdYed GdGSJQGJjLjI GdCNQi h JMOjO GdCgOGa h JcGed GdNWW GdJfajPjI h cPG JfGhd YedjI GdJZjjQ jGdJWQb Gdi GdHfGA GdeYeGQj dGMOGK GdJZjjQ h EYGOI eYGjQI ESJQGJjLjI GdehGQO GdHTQjI h GNjQG OQGSI MGdI dJWHjb GdGSJQGJjLjI (B.s
(3edGMb U(B.294s
Keywords: (3GOGQI GdGaQGOs